If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+3x+10=46
We move all terms to the left:
9x+3x+10-(46)=0
We add all the numbers together, and all the variables
12x-36=0
We move all terms containing x to the left, all other terms to the right
12x=36
x=36/12
x=3
| 3.111111x=1.666667 | | 3-13x=29 | | X/7+x/14=9 | | 11x-9=4x+9 | | ⅓x-1=½x+2 | | |3x-4|=|-x-18| | | 0.331x-1=0.5x+2 | | 6x2-75=0 | | 3+x=2.25 | | 8=4+5a | | 2h=24h | | 11-3(q-4)=8q+4 | | 3x-9=-(X+3) | | 9^(x-1)=3^(1-4x) | | 4x-2=-(2x+8) | | 3(6x–4)=22x* | | (3x-11)(3x-11)=0 | | 6t-10=4+12 | | 35x/5=15 | | n^2+2n=462 | | -4u+8(u-3)=-4 | | 14=-5y+3 | | -3y+19=-14 | | 3(v-5)-7v=-19 | | 1/2f=5 | | 5t+45=20 | | -3y+19=14 | | 1/4(16-4x)=5-x | | 3x-10+x=-2(x-4)+9 | | 6x-15=-3(5-2x) | | 4x-5=2(1+2x) | | 19+49=x |